Social Media Interactions Indicators—Likes, Comments, and Shares—On User Engagement and Content Reach among Marketing Students - Gapasin, Willy; Abanilla, Cristina Paula; Andaya, Angel Izza; Bantillo, Cristy; Diodoco, Allyssa; Dumalus, Mary Ashley; Mapoy, Dianna Jane (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between social media interaction indicators, specifically likes, comments, and shares, and perceived digital marketing outcomes in terms of user engagement and content reach among Bachelor of Science in Business Administration (BSBA) Marketing Management students at the Eulogio “Amang” Rodriguez Institute of Science and Technology (EARIST)–Manila Campus. The study aimed to determine how social media interactions influence audience participation and the dissemination of digital content. It utilized a quantitative correlational research design involving 239 respondents selected through stratified random sampling. Data were gathered using a validated researcher-made questionnaire that measured social media interaction indicators and perceived digital marketing outcomes. Descriptive statistics, including frequency counts, percentages, weighted means, and standard deviations, were used to describe respondents’ perceptions, while Pearson’s r correlation coefficient at the 0.05 level of significance was employed to determine the relationships among variables. The findings revealed that respondents demonstrated evident levels of engagement through liking, commenting, and sharing social media content. Among the three interaction indicators, sharing showed the strongest relationship with user engagement (r = 0.835, p < 0.001) and content reach (r = 0.791, p < 0.001). Likes and comments also demonstrated strong positive and statistically significant relationships with both perceived digital marketing outcomes. The results indicated that social media interactions serve as important mechanisms in improving audience participation, increasing content visibility, and expanding digital reach. The study concluded that creating informative, relevant, interactive, and shareable content enhances digital marketing effectiveness. It recommends strengthening digital marketing education and developing engagement strategies that encourage meaningful user participation among students, educators, marketers, and content creators. The study supports Sustainable Development Goal (SDG) 4 – Quality Education by contributing evidence-based insights that strengthen students’ digital marketing competencies and social media communication skills. Through improved understanding of digital engagement practices, the study contributes to educational sustainability by preparing future marketing professionals for participation in the digital economy. It also supports institutional sustainability by providing localized knowledge that can guide digital marketing education and practices within higher education contexts.
Keywords: Social Media Interaction; User Engagement; Content Reach; Digital Marketing; Marketing Management Students; Pearson Correlation